Feasibility and Safety of Cone-Beam Computed Tomography Advanced Navigation to Optimize Intra-arterial Chemotherapy Infusion of Skull Base Tumors - Cornelis, Francois H.; Lis, Eric; Tabar, Viviane; Lin, Andrew (Journal of Neurological Surgery Part B: Skull Base, 2024)
Purpose To assess the feasibility and safety of cone-beam computed tomography (CBCT) advanced navigation for optimizing intra-arterial chemotherapy infusion (IACI) in patients with skull base tumors.Materials and Methods Retrospective review on 10 consecutive IACI procedures performed in five patients (four women, 1 man) over a 1-year period. The median age of the patients was 71 years (interquartile range: 34–74). During the procedures, a CBCT-based navigation software was employed to evaluate tumor perfusion and guide the infusion methods. Catheterization of the primary tumor feeding vessel was performed in seven cases when it originated from the external carotid artery, whereas a temporary balloon-assisted occlusion technique was utilized in the remaining three cases where the tumor was primarily fed by the internal carotid artery. Carboplatin, topotecan, and melphalan were injected over a 10-minute period. Fluoroscopy time, reference dose, and Kerma area product, which estimates effective dose, were analyzed.Results The technical success rate was 100%, with a median procedure length of 82 minutes (79–90). The median fluoroscopy time was 11.3 minutes (9.4–16.9), reference dose was 93.5 mGy (62–256.5), and Kerma area product was 11.6 Gy.cm2 (9.5–25.4). The median effective dose was 3.8 mSv (1.5–5.1). The median follow-up duration was 233.5 days (186.3–432). One severe adverse event was reported, involving a right brachial hematoma and brachiocephalic artery dissection related to catheterization through a type III aortic arch. Three patients exhibited disease progression, but two patients showed stable disease.Conclusion IACI for skull base tumors guided by CBCT navigation is both feasible and safe.
Keywords: cancer; IACI; CBCT; skull base tumors; interventional radiology